LEGAL PROTECTION FOR EDUCATORS AS LECTURERS FOR OBTAINING EMPLOYMENT RIGHTS - Imelda Mardayanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Legal protection for all workers/employees, especially for lecturers working under the foundation, is absolutely necessary, since there are still many cases involving the university and the foundation. These problems still continue to haunt lecturers, so it needs concerted effort to minimize existing problems. Although there are regulations governing the relations between workers/employees and employers, but at a practical level it is still not fully implemented. It is associated with several problems, one of which is the position of lecturers at the level of subordinate more than the foundation. This phenomenon will not occur when educators take advantage of the legal protection that is already regulated by legislation. This study will elaborate on legal protection for workers, especially for educators. The research method is a normative juridical approach using an approach to legislation. The results are legal protections for educators stipulated in Law No. 21 Year 2000 on the labor unions, in particular regarding the purpose of the establishment of labor unions. In addition, Law No. 13 of 2003 on Employment already protects workers/employees, including educators, namely through unions/employees.